'There's an issue there …': Signalling functions of discourse-deictic there in the history of English. (July 2018) - Lenker, Ursula
Abstract: This paper sketches the use of simple discourse-deictic there in the history of English and shows that – in contrast to the frequent and varied employment of discourse-deictic there in there -compounds such as therein, thereby or textual therefore in written genres – simple there was only rarely and restrictedly used with discourse-deictic reference until the 19th century. In Present-Day English, discourse-deictic there, as in you are wrong there, is almost exclusively found in face-to-face interaction of a particular type, which may be labelled 'issue(s)-at-debate discussion type', such as TV and radio broadcast discussions or council or staff meetings. For these communicative situations, two particular pragmatic functions are identified, both of them discourse-organizational in nature: Speakers may signal their wish to expand on or enforce an argument which has been neglected or misinterpreted in the immediately preceding discourse or they index their wish of 'end of topic (or even discourse)' by simple discourse-deictic there . These functions are linked to there being deictic, an element of the 'field of pointing', and its inherent pointing functions to a distal place/space.